Impacto das renúncias fiscais federais nas finanças públicas dos estados - o caso do Ceará - Rocha, Paulo Sérgio (2002)
The intent of this essay is to show the financial impacts created by the fiscal renunciations at the federal and state levels; and, in order to reach our objective, we show the example of the State of Ceará, where we try to high light that the fiscal renunciations is treated in several ways, be it seen as one investment incentive policy, or even, or a concession of subsidized credit linked to the ICMS payment, in which there is a amnesty of the amount of its return to the treasury. Initially this study makes a review of the evolution of the Brazilian Fiscal Federalism, its taxation system, its responsibilities and its load in relation to the Goss National Product, furthermore defining the procedures to be adopted for the transference of resources among states and the Federal Government model of incentives. Obviously the Federal Government transfers part of its taxation income to the sub national governments according to the criteria established by the Federal Constitution, in an attempt to solve the financial imbalance of the sub national governments in relation to the demand of its populace for goods and public services. Although the intent of this essay is to high light the Federal Fiscal Renunciations where these are omitted for the constitutional transference calculations, for which we make an analogy of the renunciations and fiscal incentives at a state levei, where there will be shown the Industrial Development Funds of the State of Ceará, with an approach of its fiscal benefits and credit via ICMS renunciation, putting to the public administrators and the society, some suggestions for discussion.